Vietnam roll-tastic / Maria Maisarah Mohamad Marzuki - Mohamad Marzuki, Maria Maisarah (Universiti Teknologi MARA, Kedah, 2025)
We are proud to present Vietnam Roll-tostic, a Vietnamese food brand that draws inspiration from the funky, contemporary vibe that the product evokes when consumed. The handwritten logo symbolizes the authenticity of the brand's identity and the unique experience customers hove when they savour the product. With the togline "Dip, Eat, and Repeat," Vietnam Roll-tostic offers a variety of Vietnamese roll tastes that ore sure to keep customers coming bock for more. The included Vietnamese hot icon and its annotations symbolize the food's origin in Vietnam. Vietnam Roll-tostic hos designed the Vietnamese Roll icon to showcase the product it offers to its customers. Vietnam Roll-tastic offers three kinds of Vietnamese rolls, each unique in its own way, using different kinds of ingredients, and maintaining the halal status of the product. A variety of promotional techniques, including billboards, indoor and outdoor advertisements, and proactive oversight on social media sites like lnstagram, are used to promote these products. The goal of these initiatives is to introduce a wider audience to Vietnam Roll-tastic's distinctive tale. Eating one of Vietnam Roll-tastic's rolls aims to bring joy and the goodness in the Vietnamese roll, attracting customers from all sorts of regions, bringing them together with the same interest for food.